Beta-caryophyllene as an antioxidant, anti-inflammatory and re-epithelialization activities in a rat skin wound excision model - Gushiken, Lucas Fernando Sérgio [UNESP]; Beserra, Fernando Pereira [UNESP]; Hussni, Maria Fernanda [UNESP]; Gonzaga, Murilo Tireli [UNESP]; Ribeiro, Victor Pena; De Souza, Patrícia Fernanda; Campos, Jacqueline Costa Lima; Massaro, Taís Nader Chrysostomo; Hussni, Carlos Alberto [UNESP]; Takahira, Regina Kiomi [UNESP]; Marcato, Priscyla Daniely; Bastos, Jairo Kenupp; et al. (Wiley, 2022)
The skin is a critical organ for the maintenance of the integrity and protection of the organism. When a wound occurs, a sequence of healing mechanisms is triggered to reconstruct the wounded area. β-caryophyllene is a sesquiterpene in Copaifera langsdorffii oleoresin with antioxidant and anti-inflammatory potential. On the basis of previous studies with C. langsdorffii, β-caryophyllene was selected to evaluate its wound healing potential and pharmacological mechanisms. The excision wound model was used with male Wistar rats and macroscopic, histological, immunohistochemical and biochemical analyses were performed with skin samples, comparing the β-caryophyllene-Treated group with reference drugs. The results showed macroscopic retraction of the wounds treated with β-caryophyllene. Biochemical assays revealed the antioxidant and anti-inflammatory mechanisms of the β-caryophyllene-Treated group with increasing levels of IL-10 and GPx and decreasing levels of pro-inflammatory molecules, including TNF-α, IFN-γ, IL-1β and IL-6. After β-caryophyllene treatment, immunohistochemical assays showed enhanced re-epithelialization, through the increase in laminin-γ2 and desmoglein-3 immunolabeling. β-caryophyllene also act in the remodeling mechanism, increasing the collagen content in the Masson's trichrome staining. These findings indicated the wound-healing potential of β-caryophyllene topical formulation in rat skin wounds, mediated by antioxidant, anti-inflammatory and re-epithelialization mechanisms.